SMED(Single Minute Exchange of Die) System - Afnan Abu-Alhiega; Deyala Hanbali; Nosayma Sahban; Reem Ismaeel (My University, 2012)
SMED (single minute exchange of die) was developed by Shigeo Shingo in 1950s Japan in response to the emerging needs of increasingly smaller production lot sizes required to meet the required flexibility for customer demand. The study was originally developed through the study of a die change process. Generally, SMED aims to standardize and simplify the operations. By this means, the need for special skilled workers is also minimized. Since then, the ways to improve and support the SMED technique are considered  in our study . The SMED technique is used as an element of Total Productivity Maintenance (TPM) and continuous improvement process in various studies to reach lean manufacturing , lean can be employed to design new factories or deduce measures to improve existing factories. SMED initially focus set on critical stations that have long setup times. With the application of SMED, improvements were substantial with initial data showing reduction of setup time ranging from 25% to as high as 85%. With the reduced setup time, production flexibility expanded as it was able to afford more frequent product mix changes. In addition, machine utilization and equipment went up with the reduced setup. It is indicated that SMED in other words quick changeover is still a suitable method not only for manufacturing improvement but also for equipment/die design development. For example,  investigate the die casting process that uses high productive level machines. The changeover procedure during die casting process is studied as possible area for reducing time consumption. Focus on the SMED applications for process industry plants that produce materials like paints, paper products, foods, beverages, personal care items and fiber, and apparel rather than assembled products such as refrigerators, cell phones, or automobiles following SMED methodology steps reduce inefficient times and consider human issues. There are two types of setup, internal and external (or IED and OED). The four conceptual stages of setup improvement involve the distinguishing of these two types of setup, and the converting of internal setup to external setup. Once that is done, all aspects of setup can be streamlined. At every stage, however, setup improvements can be realized. Dies were the first improvement target and the reason SMED came to be, but the thinking carries over into many other areas. SMED has to do with every kind of changeover setup, from high volume, low mix to mass production to the job shop's high mix, low volume manufacturing process. It can be used in tool and die making where each tool, die or fixture is different.